Emission study on a direct injection diesel engine powered with blends of Moringa oleifera biodiesel-diesel - Venu H.; Appavu P.; Krishnan V.; Jayaraman J.; Manimuthu M.K.; Kosinapogu S.; Vallapudi D.R. (John Wiley and Sons Inc, 2025)
The current investigation uses biodiesel extracted from Moringa oleifera seeds in a diesel engine. M. oleifera biodiesel is prepared via conventional transesterification with standard conditions (60C reaction temperature, 120min reaction time, 1% by wt. catalyst, and 7.5:1 molar ratio). The test engine is a single-cylinder air-cooled naturally aspirated direct injection diesel engine. The test engine for experimentation is operated at 100% load with different engine speeds ranging from 1000 to 2400rpm. Emissions characteristics were analyzed at different engine speeds. Results were interesting as the MB10 blend (10% M. oleifera biodiesel + 90% diesel) lowered the smoke by 24% and hydrocarbon by 10.34% with respect to neat diesel. Almost all the test fuels have higher HC profiles at reduced engine speeds. The MB20 blend lowered the CO profile to the CO profile of diesel fuel by about 0.84%. However, it can be observed that the MB10 blend's average CO profile is improved by 1.97% than mineral diesel. These results are compromised with higher CO and NOx profiles of 2.4% and 8.9%, respectively. ? 2023 Wiley Periodicals LLC.